KAJIAN EKOLINGUISTIK SIKAP MAHASISWA TERHADAP UNGKAPAN PELESTARIAN LINGKUNGAN DI UNIVERSITAS NEGERI SEMARANG - Yuniawan, Tommi; Masrukhi, Masrukhi; Alamsyah, Alamsyah (Badan Pengembang Konservasi UNNES, 2014)
Semarang State University became University of Conservation on 12 March 2012. This influences the policy-making as well as efforts in socializing and empowering the entire campus community in creating and cementing this conservation vision. There are some mottoes that are used to uphold the principle of protection, preservation, utilization and sustainable development of natural resources and cultural arts, in order to preserve the environment of this conservation campus, for example,